2018
DOI: 10.1001/jamapsychiatry.2018.1581
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Population Density and Genetic Risk for Schizophrenia

Abstract: The results of this study appear to support the hypothesis that individuals with increased genetic risk tend to live in urban/dense areas and suggest the need to refine the social stress model for schizophrenia by including genetics as well as possible gene-environment interactions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 56 publications
5
68
1
1
Order By: Relevance
“…20 To enhance our causal understanding, 4 recent studies have investigated whether observed associations between neighborhood characteristics and schizophrenia are the results of genetic predisposition. [22][23][24][25] For example, a recent Danish study found that greater polygenic risk scores (PRS) for schizophrenia were associated with increased odds of living in urban environment at age 15 years, 22 in line with 2 other studies. 23,25 However, only 1 study has considered whether PRS for schizophrenia is associated with urban birth, finding no association with settlement size in Denmark.…”
Section: Introductionsupporting
confidence: 60%
“…20 To enhance our causal understanding, 4 recent studies have investigated whether observed associations between neighborhood characteristics and schizophrenia are the results of genetic predisposition. [22][23][24][25] For example, a recent Danish study found that greater polygenic risk scores (PRS) for schizophrenia were associated with increased odds of living in urban environment at age 15 years, 22 in line with 2 other studies. 23,25 However, only 1 study has considered whether PRS for schizophrenia is associated with urban birth, finding no association with settlement size in Denmark.…”
Section: Introductionsupporting
confidence: 60%
“…Variables/purpose Clinical and biological OPCRIT 4 a [1,2] Research diagnosis c Nottingham Onset Scale a [3] Onset of psychotic symptoms Date of first contact with services Medicated treatment start date for psychosis Duration of untreated psychosis Record of clinical diagnosis Schedule for deficit syndrome a [4] Presence of any deficit syndrome Community assessment of psychic experiences b [5] Assessment of psychopathology in control participants Structured interview for schizotypy-revised b [6,7] Assessment of schizotypy in control participants Global assessment of functioning scales a,b [8] Severity of symptoms Impairment of function Family interview for genetic studies a, b [9] Family history of psychosis or other mental illness in first degree relatives of the proband Medication list a, b Past and present medication use Premorbid Adjustment Scale-shortened a,b [10,11] Child and adolescent social adjustment Child and adolescent academic adjustment Adolescent sexual adjustment Blood sample and cheek swabs a,b DNA Socio-demographic MRC socio-demographic schedule-modified a,b [12] Age, gender, and Childhood experiences of care and abuse a,b [13,14] Number of household arrangements Separation from or death of parents Other adverse events (taken into care, excluded from school, run away from home, physical neglect) Absence of peer or adult supports Perceived loneliness Household discord Childhood abuse (physical, sexual, emotional) Amended Bullying Questionnaire a,b [15,16] Victim of childhood bullying Childhood Trauma Questionnaire a,b [17] Abuse (physical, sexual, emotional) Neglect (physical, emotional) List of threatening events a, b [18,19] Stressful events and difficulties in the year prior to onset (cases), prior to interview (controls) Social environment assessment tool a,b [20] Subjective rating of participant's neighbourhood (e.g. trust and cooperation) Major Experiences of Discrimination Scale a,b [21,22] Lifetime exposure to discrimination Cannabis Experience Questionnaire-modified a,b [23] Detailed use of cannabis (past and present) and other recreational drugs CIDI-tobacco and alcohol list a,b [24] Present alcohol and tobacco use Bologna migration history a,b [25] Migration history Deva...…”
Section: Instrumentsmentioning
confidence: 99%
“…For example, recent evidence has failed to show a universal association between city living and psychosis [19,20]. To further add to this conundrum, Colodro-Conde et al [21] found that the high prevalence of psychosis in some urban areas may be due to gene-environment selection, such that individuals with higher genetic loading for psychosis live in more densely populated areas. More generally, this points to a major limitation to our current knowledge of psychotic disorders: we know that environments affect onset and outcomes, but research so far has been conducted-with some important exceptions-in a remarkably small number of settings (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the green space assessed by the normalized difference vegetation index (NDVI) based on remote sensing data has been linked to human health [44,45], and the lifelong exposure to greenness has been associated with GMV differences in children [7]. In addition, several macro-environmental measurements derived from national survey databases, such as population density, local GDP per capita, medical supply, and educational resources have also been associated with human health [46][47][48].…”
Section: Environmental Factors Associated With Neuroimaging Phenotypesmentioning
confidence: 99%